179k views
16 votes
Solve the equation -6(2a + 7) = -22- 8a

User Matas
by
5.7k points

2 Answers

11 votes

Answer:

a=-5

Explanation:

Here you go mate

PEMDAS: Parenthesis,Exponent,Multiplication,Division,Addition,Subtraction

Step 1

-6(2a + 7) = -22- 8a Equation/Question

Step 2

-6(2a + 7) = -22- 8a Remove parenthesis

-12a-42=-8a-22

Step 3

-12a-42=-8a-22 Add 8a to the sides

-4a-42=-22

Step 4

-4a-42=-22 Subtract 42

4a=20

Step 5

4a=20 Divide both sides by 4

answer

-5

User Ewelina
by
6.5k points
5 votes

Answer: a = -5

Explanation:

First, open up the brackets, and solve it

-12a -42 = -22 -8a. (-6 x 2a, and -6 x 7)

bring the -8a to the left side, so that all the a’s are together

-12a -42 + 8a = -22 (add -42 on both sides like we did with -8a)

-12a + 8a = -22 + 42

solve

-4a = 20

divide -4 on both sides

a = -5

User Tom Tresansky
by
6.2k points